Yield and economics of soybean based cropping systems as influenced by different cropping systems, crop establishment method and residue management practices: Yield and economics of soybean based cropping systems as influenced by different cropping systems, crop establishment method and residue management practices - R K VERMA; M RAGHAVENDRA; S D BILLORE; A RAMESH; SHIVANI NAGAR; N KHANDEKAR (Journal of Oilseeds Research, 2020)
Significantly higher yield of soybean was registered under soybean-chickpea system. The increase in yield was up to 21.5% under permanent broad bed and furrow (PBBF) + residue retention (R) and 14% under PBBF + without R (WR) as compared to conventional flatbed (CTFP) + WR. Similarly, significantly higher yield of wheat and chickpea were registered under PBBF + R followed by PBBF + WR.